PENGARUH GAYA KEPEMIMPINAN TERHADAP KINERJA PEGAWAI PADA DINAS PARIWISATA KABUPATEN LOMBOK TIMUR - Harianti, Nopi; Yasintha, Nomy; Winaya, Ketut (CITIZEN CHARTER, 2024)
A good management style with decisive leaders and proper leadership styles is one of the aspects that can enhance the underperforming performance of government employees, particularly addressing timeliness difficulties. This study uses a quantitative methodology and a correlation approach to look at the relationship between leadership style (variable X) and employee performance (variable Y) at the East Lombok Tourism Board. 70 employees were given questionnaires to complete in order to gather the main data for this study. With an R2 value of 0.877, the findings demonstrate that the leadership style used at the East Lombok Regency Tourism Office has a favorable effect on employee performance. Furthermore, the findings using simple linear regression show that at the East Lombok Regency Tourism Office, improving leadership style by 1% can boost staff performance by 44.1%. The tcount (8.448) is higher than the ttable (1.669), and the significance level of the test is 0.000, showing that the leadership style of the East Lombok Tourism Board has a significant and favorable impact on employee performance.